(3OQGSI JCUjdjI heQGLYI JbjjejI Ydi VhA GdeSJLOGJ GdYdejI hGdJMhdGJ GdhbGFYjI s - (3UGdM(B, (3UGdMjs ((3GdLRGFQ(B:s (3GdOGQ GdLRGFQjI ddfTQ hGdJhRjY(B,s, 2020)
(3JfGhd gPG GdcJGH CSGSjGJ GdeGdjI hGdGbJUGO GdGSdGej ef NdGd YTQI aUhd cGdBJj(B: ((3WHjYI GdGbJUGO GdGSdGej hNUGFUg GdefgGLjI hechfGJg GdfXGejI, WHjYI GdeTcdI GdGbJUGOjI hCSHGHgG hYdGLgG aj GdEbJUGO GdGSdGej, UjZ GdGSJKeGQ hCSGdjH GdJehjd aj GdGbJUGO GdGSdGej Hjf GdSdGeI GdGSJKeGQjI hGdeSJLOGJ GdJWHjbjI , caGAI UjZ GdGSJKeGQ hCSGdjH GdJehjd aj GdGbJUGO GdGSdGej hBaGbgG GdJWHjbjI , GdbWGY GdYGe aj GdGbJUGO GdGSdGej Hjf YfGUQ GdSdGeI hOQGSGJ GdLOhi GdJcejdjI ddGSJKeGQGJ GdYGeI fXQjI GdEfJGL aj GdGbJUGO GdESdGej , fXQjI GdGSJgdGc hXhGHW GdfTGW GdJLGQj GdJShjbj aj GdGbJUGO GdESdGej JhRjY GdKQhI hGdONd aj GdGbJUGO GdESdGej(B.) (3eaghe GdCehGd hebGUOgG hWHjYI GdedcjI hCTcGdgG VhGHW GdedcjI hhVGFagG hecGfI GdbWGYGJ GdGbJUGOjI aj GdGbJUGO GdGSdGej eONd dJUfja GdMGLGJ hJQJjH GdChdhjGJ aj GWGQ GbJUGO GdChdhjGJ hGbJUGO GdehGRfGJ OhQ GdOhdI hhVGFagG heLGdGJ JONdgG aj GdGbJUGO GdGSdGej s
(3GdeQGLY U(B.557 (3agQS GdLOGhd hGdQShe GdHjGfjI U(B.571 (3agQS GdCTcGd GdJhVjMjI U(B.572s
Keywords: (3GdEbJUGO GdESdGejs